Examining Sufi Practices on Social Media: Distortions and Complexities in Contemporary Pakistan - Waheed, Usman; Junejo, Safiullah; Numan, Muhammad (Jurnal Sosiologi Reflektif, 2024)
The engagement of Sufism on Pakistani social media has sparked many concerns over the inclusivity of religious manifestations and the interpretation of the Qur'an. This research seeks to examine the historical development and objectives of Sufism in order to analyse the impact of Sufi activities in the digital domain, specifically focusing on the emergence of religious aberrations. The research was carried out utilizing qualitative methodologies by examining ancient Sufi literature and subsequently comparing it with Sufi practices in the digital domain. The findings demonstrate that internet platforms have fundamentally transformed the availability and dissemination of Sufi teachings, allowing an unparalleled avenue for dialogue and cultural manifestation that was before unachievable. Nevertheless, there are deficiencies in their attitude to community, instructional methods, and the impact of technology on their individual activities. The concept of Digital Sufism demonstrates the integration of traditional practices into the online world, resulting in both opportunities and challenges in the modern day. Praktik Sufi di media sosial Pakistan telah menimbulkan beberapa masalah terkait keberagaman dalam ekspresi keagamaan dan pemahaman terhadap teks Al-Qur’an. Melalui penelusuran sejarah dan tujuan tasawuf, penelitian ini bertujuan untuk melihat bagaimana praktik Sufi di ranah digital tersebut memunculkan distorsi keagamaan. Penelitian dilakukan dengan menggunakan metode kualitatif melalui studi literatur Sufi klasik dan kemudian membandingkannya dengan praktik sufi di ranah digital. Hasil penelitian menunjukkan platform online telah merevolusi aksesibilitas dan penyebaran ajaran Sufi, mendorong sebuah cara yang belum pernah terjadi sebelumnya untuk percakapan dan ekspresi budaya yang sebelumnya tidak mungkin tercapai. Namun, kesenjangan muncul dalam pendekatan mereka terhadap komunitas, teknik pengajaran, dan pengaruh teknologi terhadap praktik mereka masing-masing. Sufisme Digital mencontohkan asimilasi adat istiadat konvensional ke dalam ranah virtual, yang melahirkan prospek dan kompleksitas di era kontemporer.